Reaction forces of laminated glass windows subject to blast loads - Hari Arora (Composite Structures, 2015)
Several blast trials on laminated glass windows have been performed in the past, using both full field 3D Digital Image Correlation and strain gauges located on the supporting structure to collect information on the glass pane behaviour. The data obtained during three blast experiments were employed to calculate reaction forces throughout the perimeter supports both before and after the fracture of the glass layers. The pre-crack experimental data were combined with finite element modelling results to achieve this, whilst solely experimental results were employed for post-cracked reactions. The results for the three blast experiments were compared to identify similarities in their behaviour. It is intended that the results can be used to improve the existing spring–mass systems used for the design of blast resistant windows.